Guideline for Grassroots Social and Economic Development by Using the Northeastern Way of Life to Integrate Public Participation in Cultural Tourism of Khong River in Central and Northern Areas - Palapin, Pennapa; Horsaengchai, Suwannee (วารสารสันติศึกษาปริทรรศน์ มจร, 2024)
The objectives of this research article aimed: 1) to find guidelines for grassroots social and economic development by using the northeastern way of life to integrate public participation in the cultural tourism of Khong River in central and northern areas, and 2) to design guidelines for grassroots social and economic development by using the northeastern way of life to integrate public participation in the cultural tourism of Khong River in central and northern areas. The qualitative data were collected from interviewing with a sample group of 90 persons via semi-structured interview. The key informants and focus groups included representatives of people, government, and private sectors. The results of the study are as follows: 1) Guidelines for grassroots social and economic development by using the northeastern way of life to integrate public participation in the cultural tourism of Khong River in central and northern areas reveal that people have been significantly affected by development. For the tourism dimension, development must be a balance between the way of life and tourism development, which must include the ancestors of the villagers, tourism that brings prosperity to the local community through income and other investments, and other creative tourism activities. 2) The guidelines for grassroots social and economic development through the utilization of the northeastern way of life must integrate a total of 20 products of a community's local identity, which include social capital, culture and local resource capital. The participation of the people and government sectors can be done by integrating the concept of sustainable social and economic development, i.e. emphasizing joint thinking, planning, acting, following, judging and benefiting.